2018
DOI: 10.1177/2331502418765414
|View full text |Cite|
|
Sign up to set email alerts
|

Immigration Detention, Inc.

Abstract: This article addresses the influence of economic inequality on immigration detention. The US Department of Homeland Security (DHS) detains roughly 350,000 migrants each year and maintains more than 30,000 beds each day. This massive detention system raises issues of economic power and powerlessness. This article connects, for the first time, the influence of economic inequality on system-wide immigration detention policy as well as on individual detention decisions. The article begins with a description of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…Collaboration with ICE is financially lucrative because it guarantees full jails funded with federal dollars. One study participant reported the Orange County sheriff had said in a meeting that getting an ICE detention center was the best economic thing ever for the county jails (Gilman and Romero 2018).…”
Section: How Can a Traffic Stop Lead To Deportation? The Greenlight Law Should Help Immigrant Parents And Their Us Citizen Childrenmentioning
confidence: 99%
“…Collaboration with ICE is financially lucrative because it guarantees full jails funded with federal dollars. One study participant reported the Orange County sheriff had said in a meeting that getting an ICE detention center was the best economic thing ever for the county jails (Gilman and Romero 2018).…”
Section: How Can a Traffic Stop Lead To Deportation? The Greenlight Law Should Help Immigrant Parents And Their Us Citizen Childrenmentioning
confidence: 99%
“…Yet detention infrastructure is not limited to the physical structures where migrants are held. It also includes transportation systems, immigration courts, and the punitive aspects of immigration enforcement that facilitate detention and deportation (Gilman and Romero 2018). It is further characterized by lack of or delayed access to sufficient medical care, a recurrent problem indicated in institutional reports (DHS-OIG 2019a, 2019b; CDC 2021) and a theme of our interviews.…”
Section: The Infrastructure Of Detentionmentioning
confidence: 99%
“…Internal investigations conducted by the Department of Homeland Security (DHS) — ICE’s parent agency — and the Inspector General have repeatedly raised concerns about conditions and safety at these facilities, including with regard to medical care and pandemic preparation (DHS-OIG 2016, 2019a, 2019b). Researchers have reported extensively on detention facilities pre-COVID, emphasizing poor conditions, lack of oversight, profit-seeking management, and the punitive treatment of detainees (Golash-Boza 2009; Doty and Wheatley 2013; Conlon and Hiemstra 2014; Freed Wessler 2016; Gilman and Romero 2018; Hiemstra 2019). Research has also shown detention to inhibit due process for migrants facing deportation in immigration court, making them less likely to secure legal representation, less likely to win relief from deportation, and more likely to self-deport, as compared to migrants who are on the non-detained docket throughout their proceedings (Kalhan 2010; Eagly and Shafer 2015; Ryo 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The privatization—and profitability—of immigration enforcement and related services has garnered significant scholarly attention of late (e.g., Ackerman et al, 2014; Chacón, 2017; Gilman & Romero, 2018), however, the role non-profits play in immigration enforcement has been largely ignored. While private contractors participated in family separation, nonprofits that contract with ORR to care for unaccompanied children played a crucial role without which family separation might not have been possible.…”
Section: Reframing Family Separation and State-corporate Crimementioning
confidence: 99%